Adaptive robust sliding mode trajectory tracking control for 6 degree-of-freedom industrial assembly robot with disturbances. Issue 3 (6th August 2018) - Pan, Li; Bao, Guanjun; Xu, Fang; Zhang, Libin
Abstract : Purpose: This paper aims to present an adaptive robust sliding mode tracking controller for a 6 degree-of-freedom industrial assembly robot with parametric uncertainties and external disturbances. The controller is used to achieve both stringent trajectory tracking, accurate parameter estimations and robustness against external disturbances. Design/methodology/approach: The controller is designed based on the combination of sliding mode control, adaptive and robust controls and hence has good adaptation and robustness abilities to parametric variations and uncertainties. The unknown parameter estimates are updated online based on a discontinuous projection adaptation law. The robotic dynamics is first formulated in both joint spaces and workspace of the robot's end-effector. Then, the design procedure of the adaptive robust sliding mode tracking controller and the parameter update law is detailed. Findings: Comparative tests are also conducted to verify the effectiveness of the proposed controller, which show that the proposed controller achieves significantly better dynamic trajectory tracking performances as compared with conventional proportional derivative controller and sliding mode controller under the same conditions. Originality/value: This is a new innovation for industrial assembly robot to improve assembly automation.